A resin sand control composition and its application

By using the resin sand -controlled composition to form a blocking layer in volume fracture, the problem of supporting agent reflux caused by the unclean pressure of the upper part of the cracks is solved, and the effect of effectively prevent return and maintain high infiltration capabilities.

CN116676076BActive Publication Date: 2025-01-24BEIJING STILAIBO OIL & GAS TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310669283.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-07
Publication Date
2025-01-24
Estimated Expiration
2043-06-07

AI Technical Summary

Technical Problem

During the volume fracturing process, no closing pressure on the upper part of the crack causes proppant to flow back, affecting the reservoir permeability and diversion capacity, and the effectiveness and sustainability of existing control technologies are poor.

Method used

Develop a resin sand control composition, including epoxy resin, propylene oxide phenyl ether, cementing agent, degradable polymer, carbonate powder and chlorine salt powder, which is pumped into the formation and then solidified to form a sealing layer. Prevent proppant backflow.

Benefits of technology

This composition can effectively prevent the backflow of proppant and maintain a high oil-water seepage capacity without closing pressure. The construction process is simple and safe, and does not affect post-pressure flowback and production processes of oil and gas fields.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a resin sand control composition and its application. The resin sand control composition comprises epoxy resin, propylene oxide phenyl ether, a consolidating agent, a degradable polymer, carbonate powder and chloride powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oilfield sand control, and in particular to a resin sand control composition and application thereof. Background Art

[0002] At present, during the post-pressure flowback and production process of oil and gas fields, the serious problem of proppant reflux is often faced. On the one hand, proppant reflux will affect the generated fractures, cause reservoir damage, and reduce the permeability and conductivity of the reservoir. On the other hand, it will also cause damage to production equipment, injection sticking, sand burying of pipe columns and other problems. Therefore, the problem of proppant reflux needs to be effectively prevented and controlled.

[0003] As reservoir development gradually shifts from conventional to unconventional low-permeability and tight reservoirs, volume fracturing is more commonly used in fracturing methods. Volume fracturing improves the seepage characteristics and seepage capacity of the reservoir by forming a complex fracture network different from conventional fracturing, thereby effectively transforming the reservoir. At present, horizontal well fracturing is large-scale and takes a long time to drain. The staged fracturing of horizontal wells mostly adopts a one-time flowback after fracturing, which makes it more likely for proppant reflux to occur during the flowback. Compared with conventional fracturing methods, the current horizontal well volume fracturing has the characteristics of large displacement, large sand volume, and large liquid volume, which makes the proppant severely polish the near-well cracks, expand the near-well cracks, and easily form a larger crack space, making the cracks difficult to close. Fracturing fluids are mostly low-viscosity slick water for fracturing and sand carrying, which has poor sand carrying capacity and makes proppant more likely to deposit in the lower part, making dynamic fractures approximately equal to propped fractures. With the end of fracturing and sanding, the proppant in the middle and upper parts of the fractures is basically not affected by the closing pressure and is in a natural flow state, resulting in a considerable amount of proppant flowing back under its own gravity during the flowback and production process, aggravating the proppant spitting phenomenon after fracturing, increasing the cost of post-fracturing action, and having a great impact on the production of oil and gas wells in the later stage. At present, conventional proppant reflux control technologies mainly include fracture forced closure technology, resin proppant sand control and fiber sand support. Fracture forced closure technology is suitable for reservoirs with closure pressure in the formation, but not for the actual reservoir conditions under current large-scale volume fracturing. After resin-coated proppant and fiber sand proppant are injected into the formation, they need to have a certain reservoir temperature and pressure to take effect. Although there is a certain plugging effect, the effectiveness and sustainability of the effect are poor, and both methods are prone to reduce the conductivity of the fracture and affect the permeability of the reservoir. A solution to this phenomenon needs to be found.

[0004] Therefore, in view of the situation that there is no closing pressure on the upper part of the fracture during volume fracturing, it is of great significance for oil extraction to develop a control technology that can seal the proppant and prevent the proppant from flowing back without affecting the seepage capacity of oil and water. Summary of the invention

[0005] One of the present inventions provides a resin sand control composition, which includes epoxy resin, propylene oxide phenyl ether, a consolidating agent, a degradable polymer, carbonate powder and chloride salt powder.

[0006] In a specific embodiment, the epoxy resin is epoxy resin E51 and / or epoxy resin E128 and / or epoxy resin E144.

[0007] In a specific embodiment, the propylene oxide phenyl ether is propylene oxide phenyl ether 690 and / or propylene oxide phenyl ether 660.

[0008] In a specific embodiment, the solidifying agent is at least one of phenylenediamine, methyltetrahydrophthalic anhydride and diethylenetriamine.

[0009] In a specific embodiment, the degradable polymer is polylactic acid and / or polyglycolic acid.

[0010] In a specific embodiment, the particle size of the degradable polymer is 1 to 3 mm.

[0011] In a specific embodiment, the carbonate powder is at least one of calcium carbonate powder, sodium carbonate powder and sodium bicarbonate powder.

[0012] In a specific embodiment, the carbonate powder has a particle size of 40 to 200 meshes.

[0013] In a specific embodiment, the chloride salt powder is at least one of calcium chloride powder, potassium chloride powder and sodium chloride powder.

[0014] In one embodiment, the chloride salt powder has a particle size of 40 to 200 meshes.

[0015] In a specific embodiment, based on 100 parts by mass of the epoxy resin, the amount of propylene oxide phenyl ether is 3 to 8 parts by mass, the amount of the solidifying agent is 15 to 30 parts by mass, the amount of the degradable polymer is 10 to 30 parts by mass, the amount of the carbonate powder is 5 to 15 parts by mass, and the amount of the chloride salt powder is 3 to 8 parts by mass.

[0016] In a specific embodiment, the mass ratio of the degradable polymer to the carbonate powder is 5:1 to 2:1.

[0017] In a specific embodiment, based on 100 parts by mass of the epoxy resin, the amount of propylene oxide phenyl ether is 4 to 6 parts by mass, the amount of the solidifying agent is 17 to 22 parts by mass, the amount of the degradable polymer is 20 to 24 parts by mass, the amount of the carbonate powder is 6 to 8 parts by mass, and the amount of the chloride salt powder is 4 to 6 parts by mass.

[0018] The second invention provides the use of the resin sand control composition according to any one of the first inventions in preventing proppant backflow in the absence of closure pressure in the upper layer of near-wellbore fractures during volume fracturing.

[0019] Beneficial effects of the present invention:

[0020] The resin and sand control composition provided by the present invention aims at the problem of backflow of proppant in the upper part of the fracture without closure pressure during volume fracturing. The construction process is simple and safe. The formed plugging layer can effectively prevent the backflow of the proppant and has a high oil-water seepage capacity, and has no obvious effect on post-fracturing flowback and production.

[0021] The resin sand control composition provided by the present invention is pumped after the main sand addition of the fracturing fluid is completed and before the wellbore is replaced. The epoxy resin, propylene oxide phenyl ether and consolidating agent are pumped from an external container tank into a sand mixing truck, and the degradable polymer, carbonate powder and chloride salt powder are poured from a sand tank truck into the sand mixing truck. The two are mixed in the sand mixing truck and then injected into the formation.

[0022] The resin sand control composition provided by the present invention, after being pumped into the formation, undergoes a curing reaction under the formation temperature condition without the need for additional pressure, and can be consolidated to form a plugging layer with strong plugging ability and high compressive strength, which can effectively prevent the backflow of the proppant, and a synergistic effect occurs between the degradable polymer and the carbonate and chloride salts, so that the formed plugging layer has a higher seepage capacity.

[0023] The present invention uses a combination of resin sand control compositions to solidify at reservoir fractures in the absence of closure pressure into a plugging layer that can prevent proppant backflow and has a high permeability. The construction process is simple and safe, and can solve the problem of proppant backflow in the upper part of the fracture without closure pressure caused by the current volume fracturing construction process. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation manner does not constitute a limitation of the present invention under any circumstances.

[0025] Example 1

[0026] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0027] Example 2

[0028] 100 parts by mass of epoxy resin E51, 3 parts by mass of propylene oxide phenyl ether 690, 15 parts by mass of m-phenylenediamine, 10 parts by mass of polylactic acid with a particle size of 1 mm, 5 parts by mass of 200-mesh calcium carbonate and 3 parts by mass of 200-mesh sodium chloride powder are uniformly mixed to obtain a resin sand control composition.

[0029] Example 3

[0030] 100 parts by mass of epoxy resin E51, 8 parts by mass of propylene oxide phenyl ether 690, 30 parts by mass of m-phenylenediamine, 30 parts by mass of polylactic acid with a particle size of 3 mm, 15 parts by mass of 50-mesh calcium carbonate and 8 parts by mass of 50-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0031] Example 4

[0032] The epoxy resin E51 was replaced by the epoxy resin E44, and the rest was the same as in Example 1.

[0033] 100 parts by mass of epoxy resin E44, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0034] Example 5

[0035] The epoxy resin E51 was replaced by the epoxy resin E128, and the rest was the same as in Example 1.

[0036] 100 parts by mass of epoxy resin E128, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0037] Example 6

[0038] The propylene oxide phenyl ether 690 was replaced by propylene oxide phenyl ether 660, and the rest was the same as in Example 1.

[0039] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 660, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0040] Example 7

[0041] The m-phenylenediamine was replaced by methyltetrahydrophthalic anhydride, and the rest was the same as in Example 1.

[0042] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 660, 18 parts by mass of methyltetrahydrophthalic anhydride, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0043] Example 8

[0044] The m-phenylenediamine was replaced by diethylenetriamine, and the other steps were the same as those in Example 1.

[0045] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 660, 18 parts by mass of diethylenetriamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0046] Example 9

[0047] The polylactic acid was replaced by polyglycolic acid, and the rest was the same as in Example 1.

[0048] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polyglycolic acid with a particle size of 2 mm, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0049] Example 10

[0050] The 100-mesh calcium carbonate was replaced by 50-mesh sodium carbonate, and the 100-mesh sodium chloride powder was replaced by 50-mesh potassium chloride powder. The rest was the same as in Example 1.

[0051] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 660, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 50-mesh sodium carbonate and 8 parts by mass of 50-mesh potassium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0052] Embodiment 11

[0053] The 100-mesh calcium carbonate was replaced by 200-mesh sodium bicarbonate, and the 100-mesh sodium chloride powder was replaced by 200-mesh calcium chloride powder. The rest was the same as in Example 1.

[0054] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 660, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid with a particle size of 2 mm, 7.5 parts by mass of 200-mesh sodium bicarbonate and 8 parts by mass of 200-mesh calcium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0055] Example 12

[0056] The mass ratio of polylactic acid to calcium carbonate is 5:1, and the rest is the same as in Example 1.

[0057] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 25 parts by mass of polylactic acid with a particle size of 2 mm, 5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0058] Embodiment 13

[0059] The mass ratio of polylactic acid to calcium carbonate is 2:1, and the rest is the same as in Example 1.

[0060] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 20 parts by mass of polylactic acid with a particle size of 2 mm, 10 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder are uniformly mixed to obtain a resin sand control composition.

[0061] Comparative Example 1

[0062] The polylactic acid, 100 mesh calcium carbonate and 100 mesh sodium chloride powder are omitted, and the rest are the same as in Example 1.

[0063] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, and 18 parts by mass of m-phenylenediamine were uniformly mixed to obtain a resin sand control composition.

[0064] Comparative Example 2

[0065] No 100 mesh sodium chloride powder, otherwise the same as Example 1.

[0066] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid and 7.5 parts by mass of 100-mesh calcium carbonate were uniformly mixed to obtain a resin sand control composition.

[0067] Comparative Example 3

[0068] The polylactic acid and 100 mesh calcium carbonate are omitted, and the other parts are the same as those in Example 1.

[0069] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0070] Comparative Example 4

[0071] The particle size of the polylactic acid is 5 mm, and the rest is the same as in Example 1.

[0072] 100 parts by mass of epoxy resin E51, 4 parts by mass of propylene oxide phenyl ether 690, 18 parts by mass of m-phenylenediamine, 22.5 parts by mass of polylactic acid, 7.5 parts by mass of 100-mesh calcium carbonate and 8 parts by mass of 100-mesh sodium chloride powder were uniformly mixed to obtain a resin sand control composition.

[0073] Performance Testing

[0074] A glass tube mold (Φ25mm×100mm) was placed on a glass plate, and the resin sand control compositions prepared in each embodiment and comparative example were quickly poured into the glass tube mold. After filling, the mouth of the glass tube mold was covered with another glass plate, and then the glass tube mold filled with the resin sand control composition was sealed with a sealing bag and placed in a constant temperature water bath. It was solidified at 90°C for 24h. After the solidification was completed, the solidified material formed in the mold was taken out and processed into a cylinder with a diameter of 25mm and a length of 50mm using a core cutting machine.

[0075] The permeability of the cylinder was evaluated using a core flow tester: the experimental temperature was set at 90°C, and simulated formation water (simulated formation water composition: 2.0% KC1+5.5% NaC1+0.45% MgCl2+0.55% CaCl2) was used to displace the cylinder at a rate of 1 ml / min. The permeability of the cylinder was tested, and the results are shown in Table 1.

[0076] According to the test standard SY / T5276-2000 “Determination of flexural strength, compressive strength and gas permeability of artificial core for chemical sand control”, the compressive strength test of the cylinder was carried out, and the results are shown in Table 1.

[0077] As can be seen from Table 1, the concretions formed by the resin sand control compositions prepared from Examples 1 to 13 all exhibit high compressive strength and permeability; while the results of Comparative Example 1 show that the concretion formed without adding degradable polymer, carbonate powder and chloride powder has high compressive strength, but the system permeability is 0; the permeabilities of Comparative Examples 2 and 3 are both low, especially the permeability of Comparative Example 3 is almost negligible; indicating that the degradable polymers and carbonates and chlorides in Examples 1 to 13 have a synergistic effect. The results of Comparative Example 4 show that when the polylactic acid particle size is 5 mm, the resin sand control composition has a certain strength, but as the experimental time increases, the structure of the concretion is destroyed.

[0078] According to the experimental results in Table 1, a plugging layer having both certain compressive strength and high seepage capacity can be formed by selecting appropriate epoxy resin, propylene oxide phenyl ether, consolidating agent, degradable polymer, carbonate powder and chloride powder.

[0079] Table 1

[0080] Example Compressive strength / MPa Permeability / md Example 1 6.21 3690.65 Example 2 5.87 2899.43 Example 3 5.71 3891.23 Example 4 6.17 3552.44 Example 5 6.02 3594.25 Example 6 5.98 3666.33 Example 7 6.14 3582.91 Example 8 6.19 3669.82 Example 9 6.02 3571.43 Example 10 6.32 3784.21 Embodiment 11 6.27 3672.42 Example 12 6,43 3120.98 Embodiment 13 5.92 3782.11 Comparative Example 1 6.92 0 Comparative Example 2 6.15 1150.89 Comparative Example 3 6.33 69.24 Comparative Example 4 4.99 —(Structural damage)

[0081] Embodiment 14

[0082] The resin sand control composition of Example 1 was selected and constructed using the following process:

[0083] Step S1: Prepare a resin sand control composition: Prepare a 3m 3 A container tank is prepared, 2000 kg of epoxy resin E51, 80 kg of propylene oxide phenyl ether 690, and 360 kg of m-phenylenediamine are poured into the container tank, and mixed and stirred evenly to obtain a first composition; 450 kg of polylactic acid, 150 kg of calcium carbonate, and 160 kg of sodium chloride are poured into a sand tank truck and mixed to obtain a second composition.

[0084] Step S2: Construction preparation: according to the design requirements of the fracturing construction, after the main sand filling construction of the sand-carrying fracturing fluid is completed, prepare for the sand control construction;

[0085] Step S3: Sand control construction: Set the displacement of the sand mixer to 2m 3 / min, the first composition in the container tank and the second composition in the sand tank truck are pumped into the sand mixing truck together, and after being mixed evenly, the obtained resin sand control composition is injected into the formation.

[0086] Step S4: After the resin sand control composition is injected, the fracturing fluid base fluid is pumped in according to the designed amount of fracturing construction to replace it, and the displacement is increased to 4m 3 / min, after displacement, stop pumping, stop construction, wait for 24 hours, and release backflow. Among them, no sand spitting phenomenon occurs during the backflow process, proving that the resin sand control composition can better control the backflow of proppant; compared with the production data of adjacent wells (after the main sand filling construction of sand-carrying fracturing fluid is completed, the fracturing fluid base fluid is pumped in for displacement, that is, the sand control construction is omitted), the production data does not change significantly, proving that the resin sand control system does not affect the backflow and production process of oil and gas fields after fracturing.

[0087] The sand control system construction process of the present invention is simple and safe, and will not affect normal fracturing construction. Different resin sand control compositions can be selected for reservoirs with different temperatures, and can form a plugging layer with good compressive strength and high permeability, which can control the backflow of proppant without affecting the post-fracturing flowback and production process of oil and gas fields.

[0088] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.

Claims

1. A resin sand control composition, comprising an epoxy resin, propylene oxide phenyl ether, a coagulant, a degradable polymer, a carbonate powder and a chloride powder; based on 100 parts by mass of the epoxy resin, the amount of the propylene oxide phenyl ether is 3 to 8 parts by mass, the amount of the coagulant is 15 to 30 parts by mass, the amount of the degradable polymer is 10 to 30 parts by mass, the amount of the carbonate powder is 5 to 15 parts by mass, and the amount of the chloride powder is 3 to 8 parts by mass; in, The degradable polymer is polylactic acid and / or polyglycolic acid; The carbonate powder is at least one of calcium carbonate powder, sodium carbonate powder and sodium bicarbonate powder; The chloride salt powder is at least one of calcium chloride powder, potassium chloride powder and sodium chloride powder; The particle size of the degradable polymer is 1 to 3 mm; The particle size of the carbonate powder is 50 to 200 mesh; The particle size of the chloride salt powder is 50 to 200 meshes.

2. The resin sand control composition according to claim 1, characterized in that: The epoxy resin is epoxy resin E51 and / or epoxy resin E128 and / or epoxy resin E44.

3. The resin sand control composition according to claim 1, characterized in that: The propylene oxide phenyl ether is propylene oxide phenyl ether 690 and / or propylene oxide phenyl ether 660.

4. The resin sand control composition according to claim 1, characterized in that: The solidifying agent is at least one of phenylenediamine, methyltetrahydrophthalic anhydride and diethylenetriamine.

5. The resin sand control composition according to claim 1, characterized in that: The mass ratio of the degradable polymer to the carbonate powder is 5:1 to 2:

1.

6. The resin sand control composition according to claim 1, characterized in that: Based on 100 parts by mass of the epoxy resin, the amount of propylene oxide phenyl ether is 4 to 6 parts by mass, the amount of the solidifying agent is 17 to 22 parts by mass, the amount of the degradable polymer is 20 to 24 parts by mass, the amount of the carbonate powder is 6 to 8 parts by mass, and the amount of the chloride salt powder is 4 to 6 parts by mass.

7. Use of the resin sand control composition according to any one of claims 1 to 6 in preventing proppant backflow in the absence of closure pressure in the upper layer of near-wellbore fractures during volume fracturing.

Citation Information

Patent Citations

  • Curable proppant as well as preparation method and application thereof

    CN110079295A

  • Liquid self-supporting high-speed channel fracturing fluid and experimental method

    CN111718703A